Ambient Species Density and Gas Temperature Radial Profiles Derived from a Schlieren Technique in a Low-Frequency Non-thermal Oxygen Plasma Jet - Chamorro Garcés, Juan Camilo (2018)
A quantitative interpretation of the schlieren technique applied to a non-thermal atmospheric-pressure oxygen plasma jet driven at low-frequency (50 Hz) is reported. The jet was operated in the turbulent regime with a hole-diameter based Reynolds number of 13,800. The technique coupled to a simplified kinetic model of the jet effluent region allowed deriving the temporally-averaged values of the gas temperature of the jet by processing the gray-level contrast values of digital schlieren images. The penetration of the ambient air into the jet due to turbulent diffusion was taken into account. The calibration of the optical system was obtained by fitting the sensitivity parameter so that the oxygen fraction at the nozzle exit was unity. The radial profiles of the contrast in the discharge off case were quite symmetric on the whole outflow, but with the discharge on, relatively strong departures from the symmetry were evident in the near field. The time-averaged gas temperature of the jet was relatively high, with a maximum departure of about 55 K from the room temperature; as can be expected owing to the operating molecular gas. The uncertainty in the temperature measurements was within 6 K, primarily derived from errors associated to the Abel inversion procedure. The results showed an increase in the gas temperature of about 8 K close to the nozzle exit; thus suggesting that some fast-gas heating (with a heating rate ~ 0.3 K/μs) still occurs in the near field of the outflow.